Changes in nutritional values in diploid and triploid african catfish (Clarias gariepinus Burchell, 1822) exposed to chlorpyrifos and butachlor - Seyedjavad, Samaneh Sadat Karbalaei (2017)
Despite the widespread distribution of pesticides in aquatic environments, very little is known about the effects of contaminants on nutritional parameters in fish. Also limited information is known about the impacts of environmental stressors on polyploid organisms. This study investigated the effects of two commonly used pesticides, chlorpyrifos and butachlor, on the nutritional values of juvenile full-sibling diploid and triploid African catfish (Clarias gariepinus). In two separate experiments, diploid and triploid C. gariepinus were exposed for 21 days to three nominal concentrations of chlorpyrifos (50, 100, 150 μg/L) or butachlor concentrations (50, 100, 150 μg/L). The effect of chlorpyrifos on the skin gelatine yield and amino acid (AA) composition, and AA, fatty acid (FA), and proximate composition in the muscle of juvenile diploid and triploid C. gariepinus were investigated in the chlorpyrifos experiment. Similarly, the effect of butachlor on the skin gelatine yield and AA composition, and AA, FA, and proximate composition in the muscle of juvenile diploid and triploid C. gariepinus were investigated in the butachlor experiment. This study also compared the skin gelatine yield and AA composition, and muscle AA, FA, and proximate composition between unexposed (control) groups of juvenile diploid and triploid fish.No significant difference (p>0.05) was shown for the skin gelatine yield and AA composition, and muscle AA, FA and proximate composition between diploid and triploid C. gariepinus in the control groups of both experiments. However, the triploids contained higher levels of myristic acid (C14:0) and lower levels of docosahexaenoic acid (DHA; 22:6n-3) and total omega-3 FA in the muscle as compared to diploids only in the control groups of the chlorpyrifos experiment. For the chlorpyrifos-exposed groups (150 μg/L), there were significant reductions (p<0.05) of AA composition and protein content in the muscle of diploids while the skin gelatine yield remained unchanged. On the other hand, the skin gelatine yield of triploids exposed to chlorpyrifos was affected while the changes in AA composition of gelatine, muscle AA composition, protein, fat and ash content of the triploids were not significant (p>0.05). In addition, chlorpyrifos changed the moisture content of the diploids and the ash content of the triploids. In the chlorpyrifos-exposed groups (50 and 100 μg/L), the triploids showed higher levels of stearic acid (C18:0), docosapentaenoic acid (DPA; 22:5n-3), DHA, and total omega-3 FAs, and lower levels of palmitic acid (C16:0) in the muscle. The diploids, however, contained higher levels of palmitic acid and total saturated fatty acid (SFA). However, the level of total unsaturated fatty acid (UFA) was lower. The butachlor treatments did not alter the skin gelatine yield and AA composition in both the diploid and triploid fish. However, the changes in concentrations of some AAs, FAs, and protein content in the muscle of the diploids were more significant (p<0.05) than those of the control group. The changes of AA, most FA composition, moisture, protein, fat and ash content in the muscle of the triploids exposed to butachlor were not significant (p>0.05). This study showed the different biochemical responses of diploid and triploid C. gariepinus upon exposure to pesticides such as chlorpyrifos and butachlor. Significant (p<0.05) changes in AA, FA and protein content in the muscle of diploids following chlorpyrifos or butachlor exposure may indicate a lower adaptability of diploid C. gariepinus than triploids to environmental stressors. Meanwhile, parameters such as AA, FA, and protein content were suggested as reliable biomarkers due to their sensitivities to pesticides exposure. Triploids were heavier, longer and exhibited fewer changes in nutritional values under chlorpyrifos and butachlor exposure. Also, despite comparable gelatine yield and protein per unit of skin and muscle, heavier body weight and longer body length in triploid C. gariepinus should produce higher total gelatine, flesh and protein yield compared to diploids. Therefore, triploid C. gariepinus is more attractive in the aquaculture industry and fisheries management.